2019
DOI: 10.1002/cssc.201900519
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐Catalysed Reductive Amination of Carbonyl Derivatives with ω‐Amino Fatty Acids to Access Cyclic Amines

Abstract: An efficient method for the reductive aminationo fc arbonyl derivatives with w-aminof attya cids catalysed by an iron complex Fe(CO) 4 (IMes)[ IMes = 1,3-bis(2,4,6-trimethylphenyl)imidazol-2-ylidene] by meanso fh ydrosilylation was developed. A variety of pyrrolidines, piperidines and azepanes weres electively synthesised in moderate-to-excellent yields (36 examples, 47-97 %i solated yield) with ag ood functional group tolerance. Entry Substrate 1 Product 9 Yield [%] 1 93 2 87 3 89 4 90 5 95[a] Generalr eactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…Recently, we have developed an iron‐catalysed one‐pot preparation of N ‐substituted cyclic amines via reductive amination of carbonyl derivatives with ω ‐amino fatty acids under hydrosilylation conditions [14] . During this study, we identified that the first step of the synthesis leading to the lactams did not require iron catalyst.…”
Section: Figurementioning
confidence: 99%
“…Recently, we have developed an iron‐catalysed one‐pot preparation of N ‐substituted cyclic amines via reductive amination of carbonyl derivatives with ω ‐amino fatty acids under hydrosilylation conditions [14] . During this study, we identified that the first step of the synthesis leading to the lactams did not require iron catalyst.…”
Section: Figurementioning
confidence: 99%
“…The silylamine intermediate was generated, and piperidinone was also formed through intramolecular transamidation. N‐substituted cyclic amines were formed under hydrosilylation conditions catalyzed by the Fe catalyst [18] . In the same year, based on the similar Fe‐catalyzed reductive amination system, Darcel and co‐workers reported a highly efficient synthesis method for N‐substituted pyrrolidinones and pyrrolidines starting from levulinic acid esters and a variety of amines (Scheme 4G).…”
Section: Earth‐abundant Transition Metalsmentioning
confidence: 99%
“…Darcel's group developed a reductive amination of carbonyl derivatives 193 with ω ‐amino fatty acids 194 catalyzed by an iron complex Fe(CO) 4 (IMes) [IMes=1,3‐bis(2,4,6‐trimethylphenyl)imidazol‐2‐ylidene] 196 (Scheme 29). [46] N ‐substituted cyclic amines (including pyrrolidines, piperidines and azepanes) were selectively prepared in moderate to excellent yields with a high functional group tolerance.…”
Section: Iron‐catalyzed Synthesis Of Pyrrolidinesmentioning
confidence: 99%